2014
DOI: 10.4188/jte.60.51
|View full text |Cite
|
Sign up to set email alerts
|

Single Layered Dry Fabric Forming Simulation by Finite Element Analysis

Abstract: Automakers are gradually using more carbon fiber reinforced plastic (CFRP) in mass production cars because the developments of resin transfer molding (RTM) have reduced its cycle time to less than 10 minutes. Carbon fabrics are usually used as a reinforcement in RTM. First, dry carbon fabric is placed between forming dies. Then resin is injected into the preformed dry fabric and cured to create the final composite part. It is well known that the performance of the final composite part strongly depends on chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…11). [11] investigate the influence of fiber orientation to the bending stiffness with a meso-scale model of a fabric. FE analysis with the meso-scale model also show significant decrease of the bending stiffness if the yarns have an angle of ±45°.…”
Section: St Symposium On Compositesmentioning
confidence: 99%
“…11). [11] investigate the influence of fiber orientation to the bending stiffness with a meso-scale model of a fabric. FE analysis with the meso-scale model also show significant decrease of the bending stiffness if the yarns have an angle of ±45°.…”
Section: St Symposium On Compositesmentioning
confidence: 99%
“…[6][7][8] It has been demonstrated that modelling the bending stiffness of fabric or molten thermoplastic prepregs with conventional shell theories in commercial software is unrealistic. [8][9][10] Consequently, more accurate methods that include the bending stiffness in forming modelling are currently a key research area in the forming simulation of CoFRTP. [11][12][13][14] Furthermore, it is essential to consider the thermal-dependence characteristics in the thermo-stamping process modelling because the temperature distribution might not be uniform in the blank during the forming process.…”
Section: Introductionmentioning
confidence: 99%